Sequence and Functional Analysis of the Envelope Glycoproteins of Hepatitis C Virus Variants Selectively Transmitted to a New Host - D'Arienzo, Valentina (American Society for Microbiology, 2013)
Hepatitis C virus (HCV) remains a challenging public health problem worldwide. The identification of viral variants establishing de novo infections and definition of the phenotypic requirements for transmission would facilitate the design of preventive strategies. We explored the transmission of HCV variants in three cases of acute hepatitis following needlestick accidents. We used single-genome amplification of glycoprotein E1E2 gene sequences to map the genetic bottleneck upon transmission accurately. We found that infection was likely established by a single variant in two cases and six variants in the third case. Studies of donor samples showed that the transmitted variant E1E2 amino acid sequences were identical or closely related to those of variants from the donor virus populations. The transmitted variants harbored a common signature site at position 394, within hypervariable region 1 of E2, together with additional signature amino acids specific to each transmission pair. Surprisingly, these E1E2 variants conferred no greater capacity for entry than the E1E2 derived from nontransmitted variants in lentiviral pseudoparticle assays. Mutants escaping the antibodies of donor sera did not predominate among the transmitted variants either. The fitness parameters affecting the selective outgrowth of HCV variants after transmission in an immunocompetent host may thus be more complex than those suggested by mouse models. Human antibodies directed against HCV envelope effectively cross-neutralized the lentiviral particles bearing E1E2 derived from transmitted variants. These findings provide insight into the molecular mechanisms underlying HCV transmission and suggest that viral entry is a potential target for the prevention of HCV infection.